Rola ojców Kościoła w budowaniu społeczeństwa chrześcijańskiego w Afryce Prokonsularnej (I-V w.) - Wygralak, Paweł (Vox Patrum, 2019)
The article discusses the process of the Christianization of North Africa. The study is based mainly on the works of the early Christian authors (Tertullian, Cyprian, Lactantius, Augustine) and the decrees of the African synods. From the extant evidence it is difficult to describe the beginnings of Christianity in Africa. It seems to have arrived from Jerusalem and spread among the Jewish communities, over time expanding also among the indigenous inhabitants of Africa. The evangelization was not institutional in character, but the fruit of the life testimony of Christians, the attitude of martyrs, and the zealous work of the clergy. Care was taken first and foremost to conduct a thorough and in-depth catechesis connected with the reception of the sacrament of baptism and in preparation to the celebration of the most important liturgical feasts. Considerable role in the shaping of the Christian society was also played by the synodal activity of the Church. Regrettably, the Christian community was weakened by internal dissensions and the invasion of the Arian Vandals.